ECONOMIC AND ADMINISTRATIVE LEVERS OF REGULATION OF ENTREPRENEURSHIP IN THE REPUBLIC OF KAZAKHSTAN - R.K. Sabirovа; G.K. Makasheva; A.K. Jumaeva (Academic Journal of Physical and Chemical Sciences, 2019)
A market economy without a legal framework that establishes and enforces respect for property rights and the “rules of the game”, our free enterprise system could not exist. However, most people are not aware of the impact of the regulations or the process by which they are produced. We need the rules for the proper functioning of the economy and society, as they support the markets, protect the rights and safety of citizens and ensure the delivery of public goods and services. Companies complain that red tape hinders competitiveness, and citizens complain about the time it takes to fill out government documents. In addition, the development and enforcement of regulations also require resources for government and state administrations. Regulations may also have unintended costs when they become obsolete or incompatible with the achievement of policy objectives.